Optimizing collagen-based biomaterials for periodontal regeneration: clinical opportunities and challenges - Feng, Ye; Li, Hong-Peng (Frontiers in Bioengineering and Biotechnology, 2024)
Periodontal disease (PD) is a chronic inflammatory condition that affects the teeth and their supporting tissues, ultimately culminating in tooth loss. Currently, treatment modalities, such as systemic and local administration of antibiotics, serve to mitigate the progression of inflammation yet fall short in restoring the original anatomical structure and physiological function of periodontal tissues. Biocompatible material-based tissue engineering seems to be a promising therapeutic strategy for treating PD. Collagen, a component of the extracellular matrix commonly used for tissue engineering, has been regarded as a promising biogenic material for tissue regeneration owing to its high cell-activating and biocompatible properties. The structural and chemical similarities between collagen and components of the oral tissue extracellular matrix render it a promising candidate for dental regeneration. This review explored the properties of collagen and its current applications in periodontal regeneration. We also discussed the recent progression in collagen therapies and preparation techniques. The review also scrutinizes the pros and cons associated with the application of collagen-based biomaterials in PD treatment, aiming to pave the way for future applications of collagen-based biomaterials in the management of PD.